Impacto de exportar banano de la empresa banasolrey s.a. con su propia marca con destino a Rotterdam período 2015 - Herrera Martillo, Elizabeth Lastenia (2016)
The company Banasolrey S.A. is an exporter of bananas in Ecuador, which will meet 5 years experience, 2 of these years was engaged to provide export service and 3 years was decided to make its own brand "SEBAS" and to export it. The company is projected to other markets such as the US and Chile is one of the potential markets, we know and we know that the banana is the product most exported non-oil and you have to take the land that gives us our country. Banasolrey S.A. has sold in the Rotterdam market, that market rather buy a brand "SEBAS", so managed to win consumer confidence. The banana plant grows in good soil and climate must be tropical, humid and with a temperature of 18.5 ° C to not delay their growth, the best known and marketed is the Cavendish banana cooking banana dessert, I orito, red banana and plantain…..